di Implementasi Kebijakan Pencegahan Bullying di Perguruan Tinggi Studi Kasus Universitas Diponegoro - Zulfa Rafida Rizky; Tati; Hanifah Nur Syita; Hilyah Octavia Ramadhany; Nofitri Wulan Ramadhani; Rafilah Rafa Delima; Djoni Gunanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2026)
This study analyzes the implementation of anti-bullying policies at Diponegoro University using Edward III's theory following the tragic case of dr. Aulia Risma Lestari in August 2024. The research aims to identify supporting and hindering factors in implementing anti-bullying policies and to evaluate the effectiveness of the reporting system. The qualitative research method employs a descriptive literature study approach, utilizing secondary data from scientific journals, regulations, official reports, and media, as well as primary data through semi-structured interviews. The findings indicate that Diponegoro University has established LPKB with a multi- channel reporting system and anonymous mechanisms. However, implementation gaps exist in four aspects: uneven policy communication (only 23% of students understand the procedures), bureaucratic structure with inadequate SOPs, inconsistent implementer disposition, and resource limitations resulting in underreporting (only 3 cases recorded until November 2025). The hierarchical seniority culture in PPDS is normalized through illegal financing, excessive duties, and social exclusion. The research recommends strengthening systematic socialization, developing comprehensive SOPs, enhancing human resource capacity, conducting periodic prevalence surveys, transforming academic culture, and implementing continuous policy evaluation to create a safe and inclusive campus environment.